1997
DOI: 10.1074/jbc.272.44.28142
|View full text |Cite
|
Sign up to set email alerts
|

The Kidney Androgen-regulated Protein Promoter Confers Renal Proximal Tubule Cell-specific and Highly Androgen-responsive Expression on the Human Angiotensinogen Gene in Transgenic Mice

Abstract: Transgenic mice were generated containing a 1542-base pair fragment of the kidney androgen-regulated protein (KAP) promoter fused to the human angiotensinogen (HAGT) gene with the goal of specifically targeting inducible expression of renin-angiotensin system components to the kidney. High level expression of both KAP-HAGT and endogenous KAP mRNA was evident in the kidney of male mice from two independent transgenic lines. Renal expression of the transgene in female mice was undetectable under basal conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
134
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(138 citation statements)
references
References 36 publications
2
134
2
Order By: Relevance
“…However, our liver Agt KO study revealed that the Agt protein synthesized from the renal Agt mRNA is too low to be appreciated by either immunostaining or Western blot analysis. However, kidney Ag KO led to a decrease in urinary Agt protein, suggesting that most Agt protein synthesized in the S3 segment is immediately secreted into the urine; thus, our findings support the notion previously offered in the work by Ding et al 25 Our study also showed that, whereas disruption of kidney Agt gene has no effect on renal AII content, disruption of liver Agt gene markedly reduces renal AII. In fact, although liver Agt KO led to a moderate increase in renal Agt mRNA in a compensatory fashion, the increase was not translated into an increase in renal AII content.…”
Section: Discussionsupporting
confidence: 82%
“…However, our liver Agt KO study revealed that the Agt protein synthesized from the renal Agt mRNA is too low to be appreciated by either immunostaining or Western blot analysis. However, kidney Ag KO led to a decrease in urinary Agt protein, suggesting that most Agt protein synthesized in the S3 segment is immediately secreted into the urine; thus, our findings support the notion previously offered in the work by Ding et al 25 Our study also showed that, whereas disruption of kidney Agt gene has no effect on renal AII content, disruption of liver Agt gene markedly reduces renal AII. In fact, although liver Agt KO led to a moderate increase in renal Agt mRNA in a compensatory fashion, the increase was not translated into an increase in renal AII content.…”
Section: Discussionsupporting
confidence: 82%
“…In situ hybridization demonstrated that expression of hAGT mRNA in males and testosterone-treated females was restricted to proximal tubule epithelial cells in the renal cortex. Although there was no detectable hAGT protein in plasma, it was shown in the urine, consistent with a pathway of synthesis in proximal tubule cells and release into the tubular lumen [75]. Mouse angiotensinogen and hAGT have a similar structure; however, mouse renin is species-specific and cannot cleave hAGT [77].…”
Section: Angiotensinogenmentioning
confidence: 99%
“…Sigmund and colleagues [74][75][76] developed a series of interesting models of inducible hypertension. Transgenic mice were generated in which a fragment of the kidney-specific androgen-regulated protein (KAP) promoter was fused to the human angiotensinogen (hAGT) gene.…”
Section: Angiotensinogenmentioning
confidence: 99%
“…The specimens were then immediately centrifuged at 12,000 rpm for 2 min at 2°C, and a 50-l plasma sample was obtained and immediately frozen at Ϫ80°C. Plasma samples were treated as described previously (18,31). Radioimmunoassays were then performed using the RIANEN angiotensin I 125 I-labeled radioimmunoassay kit (Dupont) using the directions and reagents supplied by the manufacturer.…”
Section: Generation Of Transgenic Mice-mentioning
confidence: 99%